Maternal COVID-19 Exposure Risk during Pregnancy is Associated with Altered Placental Histopathology: An Exploratory Study from Kolkata, India - Mandal, Sulagna; Mukherjee, Ruchira; Bhattacharyya, Aditi; Mitra, Sukumar; Biswas, Pranab Kumar; Mukhopadhyay, Aparna (British Journal of Healthcare and Medical Research, 2026)
Background: The impact of epidemiological exposure risk to COVID-19 remains unexplored, especially in pregnant women. This study, therefore, aims to investigate how exposure risk to COVID-19 during pregnancy influences the outcome and placental histopathology. Methods: A cohort of 60 pregnant women (30 control and 30 exposed) from Calcutta Medical Hospital and Calcutta National Medical College Hospital was studied. An exposure risk scoring system was assigned based on common COVID exposure routes such as contact frequency, clinical risk factors and symptom history. Clinical parameters were recorded and correlated with histopathological findings of haematoxylin-eosin-stained placental sections. Statistical analyses included Mann-Whitney U test, Chi-square test, Odds ratio estimation and Logistic regression. Findings: Higher pregnancy complications were observed in women with higher COVID-exposure risk women (odds ratio=4.5, p<0.05). Placental abnormalities were markedly elevated in the exposed-risk group with increased fibrin deposition (73.4% vs 13.15%, p<0.01), crowding of villi (9.4% vs 0%, p<0.01) and calcification (8.9% vs 2.1%, p<0.05). Normal histology was dramatically reduced among patients with higher exposure risk (7.83% vs 67%, p<0.01). Further, correlation analysis revealed that fibrin deposition, crowding of villi and syncytial knots were positively associated. While a higher exposure risk scores correlated with alterations in placental morphology, it did not serve as an independent predictor of overall clinical outcomes within this cohort. Conclusion: Even without active infection at delivery, maternal exposure risk to COVID-19 during pregnancy could be statistically associated with specific histopathological changes in the placenta, suggesting a potential subclinical impact. The innovative exposure risk scoring model developed here provides an effective framework for quantifying infection risk and its biological implications.